A fatal retroperitoneal bleeding from iliolumbar artery following open reduction and internal fixation of an unstable pelvic ring injury: A case report. Issue 7 (17th February 2023) - Song, Suk-Kyoon; Park, Jinkyu; Lee, Sungho
Abstract : Rationale: Retroperitoneal bleedings are the result of injury to parenchymal tissue or vascular structures within retroperitoneal cavity. This may arise spontaneously, as a result of trauma or iatrogenically. Patients usually do not manifest clinically apparent signs and symptoms until a substantial amount of blood loss has occurred. Therefore, it is associated with high morbidity and mortality. Herein we present and discuss a case of fatal iatrogenic retroperitoneal bleeding following open reduction and internal fixation of an unstable pelvic ring injury. Patient concerns: A 66-year-old female patient presented to the Level I regional trauma center with severe pelvic pain after a pedestrian collision by a car. Diagnoses: In initial radiography and computed tomography, she was diagnosed with unstable pelvic ring injury. Interventions: Definitive surgery for open reduction and internal fixation through the anterior approach to the sacroiliac joint and anterior intrapelvic approach was performed on the 8th day after the injury. Outcomes: Patient died 3 days after the surgery due to a massive retroperitoneal bleeding from iliolumbar artery. Lessons: Insidious retroperitoneal bleeding from the small vessel may lead to fatal massive retroperitoneal hematoma. Therefore, active retroperitoneal bleeding should be suspected in cases of unexplained unstable hemodynamic status following orthopedic pelvic and acetabular surgery.